Character Debitur Bank Syariah dalam Memenuhi Kewajiban - Saparuddin Siregar (Universitas Darussalam Gontor, 2013)
Observing the NPF ratio of Syariah Banking which is compare with the NPL in Conventional Banking, it is found out that NPF usually higher than the NPL. Syariah Banking is a Bank which applies the Islamic morality in approaching or interacting with it’s customer. This kind of approaching will bring in or encourage a good character of customer, but it’s questionable why the NPF still high. Weber’s theory explain that there is a relationship between religion and behavior, so this research will describe what are the causal factor of NPF, what are the character’s of the debtor in sharia banking and try to analyze how the correspondence of the Weber’s theory in this field. This research is a kind of socio religious research which use statistical descriptive analysis. The population of this research is the all of sharia bank in north sumatera, which took BPRS Puduarta Insani addresses in Kabupaten Deli Serdang as a sample. Source of data are documents, records such a list of non performing financing on the Agustus 2011. Besides collecting the information through study documents, some interviews to officers and staff are conducted. The results of this study shows that the factors influenced the NPF are bad character (37%), followed by uncomfortable condition (27%) and lack of collateral (20%). capacity only influ- enced 10%, while capital only 6%. The Decreasing of NPF in BPRS by religious approach, good fight, and high pressure, have positive effect for the NPF. By this research Weber’s theory has correspondence with the empirical fact.